Ecos de las obras de Marcial y Erasmo en un eprigrama de Arias Montano durantes sus estudios en Alcalá - Pascual Barea, Joaquín, 1963- (2000)
This paper deals with an epigram, which Ariae Montanus addressed to the Cordovan theologian Petrus Serranus, one of his teachers and friends at the Complutensian University, around 1551. The language, style, structure and topics of the poem are mainly based upon Martial, while the final joke about a 'Pythagorean mea!' with the meaning of a 'frugal mea!', may be based upon a text from Erasmus' Colloquia familiaria. The article also refers to the genre of the epigram as a witty descriptive label, suitable for a gift, in Martial as well as in the Renaissance literature, and with the value and meaning of these three gifts: the olives from his fatherland (the ancient Baetica); the soles from the Atlantic Ocean, and the edible shoots of a box-thorn collected by himself in Alcalá de Henares.
Keywords: Marcial, Marco Valerio; Erasmus, Desiderius, -- 1467-1536; Arias Montano, Benito, -- 1527-1598 -- Alcalá de Henares; Epigramas